Mechanistic insights into sodium storage in hard carbon anodes using local structure probes. Issue 84 (3rd October 2016) - Stratford, Joshua M.; Allan, Phoebe K.; Pecher, Oliver; Chater, Philip A.; Grey, Clare P.
Abstract : Hard carbon anodes for sodium-ion batteries are probed using solid state NMR and pair distribution function analysis. Abstract : Operando 23 Na solid-state NMR and pair distribution function analysis experiments provide insights into the structure of hard carbon anodes in sodium-ion batteries. Capacity results from "diamagnetic" sodium ions first adsorbing onto pore surfaces, defects and between expanded layers, before pooling into larger quasi-metallic clusters/expanded carbon sheets at lower voltages.